No excess mortality among working-age Italians during the Omicron wave of Covid-19 - Alicandro, Gianfranco; Remuzzi, Giuseppe; Centanni, Stefano; Gerli, Alberto; La Vecchia, Carlo (La Medicina del Lavoro, 2022)
Background: This study provides updated estimates of the excess deaths in Italy with a focus on the working-age population. Methods: Over-dispersed Poisson regression models, fitted on 2011-2019 mortality data, and including terms for age, calendar year and a smooth function of the week of the year, were used to estimate the expected number of deaths during the Covid-19 pandemic. The excess deaths were then obtained by the difference between observed and expected deaths and reported according to the pandemic periods defined by the predominant circulating variant of SARS-CoV-2. Results: Around 170,700 excess deaths at all ages were estimated between March 2020 and March 2022 in Italy with most of the excess occurring during the pre-Delta and Delta period, and 2930 excess deaths (+2.5%) during the Omicron wave. The excesses among the working age population were: 10,425 deaths (+11.8%) during the pre-Delta period, 2460 (+9.4%) during the Delta wave, 283 (+2.2%) during the transition period to Delta. Mortality was lower than expected during the Omicron wave (-6.1%). Conclusions: Over the periods preceding the Omicron wave, Covid-19 caused around 12,800 excess deaths among individuals of working age, accounting for over 10% excess death. This excess was no longer observed during the Omicron wave.